Ecological assessment of the aftereffect of phosphogypsum on the stabilization of the carbon balance of the regenerated topsoil of degraded sod-podzolic soils - Vasenev Peter; Stepanov Andrey; Vasenev Ivan (BIO Web of Conferences, 2024)
Against the background of global climate changes, agroecological problems of erosion and agrogenic degradation of intensively used arable soils have become more acute. This problem is most acute in the case of old-arable sod-podzolic soils with initially low humus content and small thickness of their sod horizons. Our research carried out with the support of project No. 075-15-2021-1030 of the Ministry of Science and Higher Education of Russia, provides investigation the influence of industrial waste in the production of phosphorous fertilizers - phosphogypsum on the stabilization of the carbon balance of the regenerated topsoil of degraded sod-podzolic soils. The research was carried out at the Agroecological Station of the Field Experimental Station of the Russian State Agrarian University - Moscow Timiryazev Agricultural Academy in fall of 2022 and in summer of 2023. The use of phosphogypsum in a dose of 1.5 t/ha contributed to the significant accumulation of organic carbon in the topsoil of the studied sod-podzolic soils – in comparison with the control. In combination with compost from bird dropping at a dose of 2.0 t/ha, the aftereffect of the use of phosphogypsum essentially increases, that indicates good prospects for the validation of this technology as a natural climate project.